Identification of sap flow driving factors of jujube plantation in semi-arid areas in Northwest China - Xinguang, Wei; Bo, Li; Chengjiu, Guo; Youke, Wang; Jianqiang, He; Liu, Shouyang; Tieliang, Wang; Mingze, Yao (International Journal of Agricultural and Biological Engineering, 2017)
Jujube is widely cultivated in the semi-arid region of the Loess Plateau in Northwest China due to its high water deficit tolerance. In such an ecologically vulnerable area, it is critical to explore the water consumption processes of key tree species and their responses to driving factors. Sap flow data gathered during a two-year field study in a jujube plantation were analyzed as a surrogate for transpiration measurements. The measured sap flows were related to changes in the soil water content, meteorological factors (the vapor pressure deficit and the level of photosynthetically active radiation), and plant physiological factors (the sap wood area, leaf area and leaf area index). The factors that govern sap flow were found to vary depending on the growing season, and on hourly and daily timescales. The plants’ drought tolerance could be predicted based on their peak sap flows and the variation in their sap flow rates at different soil water levels. The sap flow was most strongly affected by the water content of the topmost (0-20 cm) soil layer. Of the studied meteorological factors, the photosynthetically active radiation had a greater effect on sap flow than the vapor pressure deficit. The correlation we found could be applied to predict jujube tree water consumption and assist the design of irrigation scheme.Keywords: jujube, sap flow, soil water content, photosynthetically active radiation, the Loess PlateauDOI: 10.3965/j.ijabe.20171002.2140Citation: Wei X G, Li B, Guo C J, Wang Y K, He J Q, Liu S Y, et al. Identification of sap flow driving factors of jujube plantation in semi-arid areas in Northwest China. Int J Agric & Biol Eng, 2017; 10(2): 172–183.